1988
DOI: 10.1007/bf02284051
|View full text |Cite
|
Sign up to set email alerts
|

Bone metabolism in patients with rheumatoid arthritis

Abstract: Bone metabolism in patients with rheumatoid arthritis is reviewed. Two different entities are recognised: 1) a localised periarticular bone loss, due to inflammatory processes and 2) a generalised increased bone turnover, ultimately leading to a loss of axial bone mass. The mechanism of this loss of axial bone is not completely understood; probably immobilisation is the most important factor. The influence of certain drugs is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Some have suggested that positive influences on disease activity and mobility may outweigh their deleterious effects on bone. [1][2][3][4][5][6][7] In this review we will focus on the association between generalised osteoporosis and RA, and on the effects of low dose glucocorticoid treatment on bone mass in these patients, including data that have been presented at recent scientific meetings. Abnormalities in bone metabolism and calcium regulating hormones, or strategies for the management of osteoporosis in patients with RA, are not included.…”
Section: Roland F J M Laan Piet L C M Van Riel Levinus B a Van De Pmentioning
confidence: 99%
“…Some have suggested that positive influences on disease activity and mobility may outweigh their deleterious effects on bone. [1][2][3][4][5][6][7] In this review we will focus on the association between generalised osteoporosis and RA, and on the effects of low dose glucocorticoid treatment on bone mass in these patients, including data that have been presented at recent scientific meetings. Abnormalities in bone metabolism and calcium regulating hormones, or strategies for the management of osteoporosis in patients with RA, are not included.…”
Section: Roland F J M Laan Piet L C M Van Riel Levinus B a Van De Pmentioning
confidence: 99%
“…porosis, and one-third have reduced bone mass in their hips 2 . Osteoporosis in RA is multifactorial, and its causes include medications (mainly corticosteroids); factors related to RA, such as disease activity, impairment in function with limited mobility, and cytokines that stimulate bone resorption; and general factors, such as age, female sex, and postmenopausal status 3,4 . In patients with RA, earlier identification of subgroups with low bone mineral density (BMD) and other risk factors for osteoporosis is required because the development of osteoporotic fractures in these patients is increased compared with the general population.…”
mentioning
confidence: 99%
“…The deleterious effect of inflammation on the quality of bone has been well documented in RA by local periarticular osteoporosis as well as by generalised osteoporosis 14. Generalised osteoporosis of the axial and appendicular skeleton in RA leads to an increased risk of fractures (adjusted RR for clinical osteoporotic fractures 1.5 (95% CI 1.4 to 1.6), most marked at the hip (RR 1.3) and spine (RR 2.4)) in patients without recent glucocorticoid (GC) use,15 but this increased risk is more than doubled in patients using GCs, even in low dosages (see below).…”
Section: Effects Of Inflammatory Arthritis On Bonementioning
confidence: 99%